Extensively drug-resistant tuberculosis in a young child after travel to India. Issue 12 (December 2015) - Salazar-Austin, Nicole; Ordonez, Alvaro A; Hsu, Alice Jenh; Benson, Jane E; Mahesh, Mahadevappa; Menachery, Elizabeth; Razeq, Jafar H; Salfinger, Max; Starke, Jeffrey R; Milstone, Aaron M; Parrish, Nicole; Nuermberger, Eric L; et al.
Summary: Extensively drug-resistant (XDR) tuberculosis is becoming increasingly prevalent worldwide, but little is known about XDR tuberculosis in young children. In this Grand Round we describe a 2-year-old child from the USA who developed pneumonia after a 3 month visit to India. Symptoms resolved with empirical first-line tuberculosis treatment; however, a XDR strain of Mycobacterium tuberculosis grew in culture. In the absence of clinical or microbiological markers, low-radiation exposure pulmonary CT imaging was used to monitor treatment response, and guide an individualised drug regimen. Management was complicated by delays in diagnosis, uncertainties about drug selection, and a scarcity of child-friendly formulations. Treatment has been successful so far, and the child is in remission. This report of XDR tuberculosis in a young child in the USA highlights the risks of acquiring drug-resistant tuberculosis overseas, and the unique challenges in management of tuberculosis in this susceptible population.